Happy valentine's day, Charlie Brown! - Schulz, Charles M. (Charles Monroe), 1922-2000; Testa, Maggie; Jeralds, Scott (New York, NY : Simon Spotlight, an imprint of Simon & Schuster, 2015)
As Valentine's Day approaches Charlie Brown tries to find the courage to give the Little Red-haired Girl a valentine.
At head of title: Peanuts.
Keywords: Brown, Charlie (Fictitious character) -- Juvenile fiction; Valentine's Day -- Juvenile fiction; Courage -- Juvenile fiction; Friendship -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Picture books; Brown, Charlie (Fictitious character); Courage; Friendship; Interpersonal relations; Valentine's Day; Fiction; Juvenile works